Les croisements de l’éthique et des morales entre francophonie et anglophonie à l’âge classique - Cléro, Jean-Pierre (Lumen, 2021)
During the seventeenth and eighteenth centuries, French authors did not ignore the word “éthique,” but neither did they make it play a specific role in their works like they did with “morale,” their preferred term. By contrast, English writers were more likely than their counterparts to distinguish “Ethicks” from “Morals.” Consequently, it is mainly in English-language writings that the separation of the two terms can be found. The key authors invested in refining these distinctions are Locke, Shaftesbury, Hutcheson, Hume, and Bentham—the last one being the philosopher who enacted the splitting of these two terms. From their meditations gradually emerges a belief in the conditions for a common moral platform and position; in those authors’ estimation, this foundation could properly take the place of mathematical ethical inquiry. Among those exposing utilitarianism, ethics are a matter of calculation, ethical action achievable through mathematical rules. If calculation is still limited with Hutcheson, it becomes subtler still with Bentham, even if the first utilitarian author stays within the parameters of this moral philosophy. Bentham seems to be inspired by Bayesian–Pricean probability calculus, and his main and seminal ideas are developed in “The Axioms of Pathology” at the end of the “Pannomial Fragments.”